Sistem Pakar Gangguan Tidur pada Orang Dewasa Menggunakan Metode Forward Chaining dan Certainty Factor - Rauzan Habas Addawy; Raditia Vindua (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Sleep disorders are health problems that can affect a person’s quality of life, both physically and psychologically. Many underprivileged communities face difficulties in accessing medical examinations due to financial and accessibility limitations. Therefore, a system that can assist in the preliminary diagnosis of sleep disorders is needed. This research designs and develops an expert system to diagnose sleep disorders in adults using the Forward Chaining method for rule tracing and the Certainty Factor method to calculate the certainty level of the diagnosis based on symptoms selected by the user. The system has two types of users: Admin, who manages data on symptoms, diseases, rules, and monitors diagnostic history and feedback; and User/Patient, who can consult the system to determine the possible type of sleep disorder experienced. The testing results show that the system is able to provide an initial diagnosis with a certain confidence level and offers relevant solutions and recommendations. Thus, this expert system is expected to assist the community, especially in primary healthcare facilities, in conducting early consultations on sleep disorders without high cos